The Influence of Good Corporate Governance, Profitability, and Leverage on Company Value in the Energy Sector Listed on the Indonesia Stock Exchange in 2018 - 2023 - Zidan Osca Alfansyah; Muhamad Muslih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the effect of Good Corporate Governance (GCG), profitability, and leverage on firm value among energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2018–2023. A descriptive quantitative approach with a case study design is employed, using secondary data from 45 companies, resulting in 270 firm-year observations. GCG is measured through the proportion of independent commissioners, the number of board members, and the audit committee’s size, as these elements are widely recognized in agency theory as mechanisms for monitoring managerial performance and reducing information asymmetry. Profitability is proxied by Return on Assets (ROA), leverage by the Debt-to-Equity Ratio (DER), and firm value by the Price-to-Book Value (PBV). Panel data regression analysis is applied, with model selection based on the Chow, Hausman, and Lagrange Multiplier tests, processed using IBM SPSS 25 and EViews 13. The findings indicate that the independent variables collectively exert a significant influence on firm value. Partially, audit committee size and the number of directors exhibit a negative association with firm value, while leverage has a positive effect. In contrast, the proportion of independent commissioners and profitability show no significant relationship. These results emphasize that firm value in the energy sector is more strongly shaped by governance mechanisms and financial structure than by profitability performance.